2020
DOI: 10.3390/rs12152347
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent and Lagged Effects of Extreme Drought Induce Net Reduction in Vegetation Carbon Uptake on Tibetan Plateau

Abstract: Climatic extremes have adverse concurrent and lagged effects on terrestrial carbon cycles. Here, a concurrent effect refers to the occurrence of a latent impact during climate extremes, and a lagged effect appears sometime thereafter. Nevertheless, the uncertainties of these extreme drought effects on net carbon uptake and the recovery processes of vegetation in different Tibetan Plateau (TP) ecosystems are poorly understood. In this study, we calculated the Standardised Precipitation–Evapotranspiration Index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 81 publications
1
22
0
Order By: Relevance
“…The favorable water and heat environment provided important resources for vegetative growth [37,38]. Water supply determines whether the photosynthesis occurs normally with an adequate CO 2 concentration and sufficient light [24,39]. Meanwhile, water is also an indispensable intermediary used to ensure nutrient substance transport [24,40].…”
Section: Spatial-temporal Patterns Of Plant Phenologymentioning
confidence: 99%
“…The favorable water and heat environment provided important resources for vegetative growth [37,38]. Water supply determines whether the photosynthesis occurs normally with an adequate CO 2 concentration and sufficient light [24,39]. Meanwhile, water is also an indispensable intermediary used to ensure nutrient substance transport [24,40].…”
Section: Spatial-temporal Patterns Of Plant Phenologymentioning
confidence: 99%
“…Guo et al concluded, by studying the trend of the evapotranspiration index of standard precipitation in China, that winter and spring in the TP will become drier in the 21st century [37]. Ye et al further found that the frequency of extreme drought events in the Qaidam Basin is the highest (3-6 times) in the TP [38]. Wang et al considered that drought is caused by a decrease in precipitation and an increase in temperature [39].…”
Section: Introductionmentioning
confidence: 99%
“…SPEI-12 during the non-growing season was not considered because the highest correlations between drought events and vegetation response occurred in the growing season [32,43,60]. In addition, the non-growing season was the dormant period for plants, which caused only a small impact on NDVI max , and taking it into account could result in erroneous information; (2) multiple drought events of less than 3 intervening years were integrated into a single drought event, considering the potential lag effects of drought and ensuring a recovery time of at least 3 years after a drought event [34,61]. It was considered a drought year if there was a drought event in that year.…”
Section: Identifying Drought Eventsmentioning
confidence: 99%